Проточная часть осевой турбины как объект интегрированного информационного пространства САПР "Турбоагрегат" - Усатый, Александр Павлович (НТУ "ХПИ", 2010)
In article the complex of methods and algorithms connected with development and improvement of information model of the axial turbine flow path is described. The highperformance mechanism of navigation on a hierarchical information space of the flow path project is proposed. Methods and algorithms ensuring operation of an algorithmic part of multidisciplinary calculation models of axial turbine flow path directly with data from the project hierarchically structured information space are considered.
Keywords: САПР; проточная часть; осевая турбина; информационная модель; объект проектирования; сложный технический объект